Welder’s lung and brain MRI findings in manganese-exposed welders: occupational diseases of welders - Alici, Nur Şafak; Nadir Öziş, Türkan; Çeliker, Gülay; Birlik Aktürk, Tülin (La Medicina del Lavoro, 2022)
Background: Biomarkers of manganese (Mn) exposure and manganism are poorly understood. Blood Mn levels are often used to assess exposure, while brain Mn accumulation may be demonstrated by pallidal hyperintensity at magnetic resonance imaging (MRI). Mn-containing electrodes used in manual metal arc welding may be associated with the welder’s lungs. Methods: A cross-sectional study was set up to compare T1 intensity in basal ganglia at MRI and Mn blood levels in subjects with or without pneumoconiosis. Clinical, radiological, pulmonary function and laboratory parameters were assessed among 154 welders referred to our hospital for suspected pulmonary pathology. Results: The study group included 123 male welders with pneumoconiosis (79.9%) and 31 welders without pulmonary damage (20.1%). The cases without pneumoconiosis were younger (38.5±6.6 vs 42.1±7.1, p=0.012). Cases with pneumoconiosis had blood lower Mn levels [13.5 (10-21)] as compared to those without pneumoconiosis [18.5 (7.8- 34)], p=0.035. In the same groups, the cases with high blood Mn levels were 49 (39.8%) and 18 (58.1%) p= 0.052, respectively. Brain MRI hyperintensity was found in 86 (55.8%) subjects with welder’s lung 63 (51.2) but also in 23 (74.2) individuals without welder’s lung. MRI hyperintensity in basal ganglia was significantly related to high blood Mn (p<0.005). Conclusion: This is the first study evaluating blood Mn levels of welders and their correlation with pulmonary and neurological effects. Poor working conditions may be associated with exposure to Mn and fibrogenic fumes leading to chronic lung diseases and hyperintensity in brain MRI suggesting Mn accumulation.